The prognostic significance of specific HOX gene expression patterns in ovarian cancer. Issue 7 (14th June 2016) - Kelly, Zoe; Moller‐Levet, Carla; McGrath, Sophie; Butler‐Manuel, Simon; Kavitha Madhuri, Thumuluru; Kierzek, Andrzej M.; Pandha, Hardev; Morgan, Richard; Michael, Agnieszka
Abstract : HOX genes are vital for all aspects of mammalian growth and differentiation, and their dysregulated expression is related to ovarian carcinogenesis. The aim of the current study was to establish the prognostic value of HOX dysregulation as well as its role in platinum resistance. The potential to target HOX proteins through the HOX/PBX interaction was also explored in the context of platinum resistance. HOX gene expression was determined in ovarian cancer cell lines and primary EOCs by QPCR, and compared to expression in normal ovarian epithelium and fallopian tube tissue samples. Statistical analysis included one‐way ANOVA and t ‐tests, using statistical software R and GraphPad. The analysis identified 36 of the 39 HOX genes as being overexpressed in high grade serous EOC compared to normal tissue. We detected a molecular HOX gene‐signature that predicted poor outcome. Overexpression of HOXB4 and HOXB9 was identified in high grade serous cell lines after platinum resistance developed. Targeting the HOX/PBX dimer with the HXR9 peptide enhanced the cytotoxicity of cisplatin in platinum‐resistant ovarian cancer. In conclusion, this study has shown the HOX genes are highly dysregulated in ovarian cancer with high expression of HOXA13, B6, C13, D1 and D13 being predictive of poor clinical outcome. Targeting the HOX/PBX dimer in platinum–resistant cancer represents a potentially new therapeutic option that should be further developed and tested in clinical trials. Abstract : What's new? Homeobox ( HOX ) genes, which serve key functions in DNA repair and cell differentiation, are aberrantly expressed in ovarian cancer. How they influence the disease, however, remains enigmatic. Here, a five‐gene signature, involving elevated expression of HOXA13, B6, C13, D1 and D13, was found to predict poor clinical outcome in epithelial ovarian cancer . Meanwhile, platinum resistance in high grade serous ovarian cancer cells was linked to HOXB4 and HOXB9 overexpression. In mice, treatment with HXR9, a peptide that disrupts interactions between HOX and co‐factor PBX, effectively recovered cisplatin sensitivity in resistant tumors, opening the path to novel therapeutic options in ovarian cancer.